Craft Your Sales Pitch with Competitive Differentiation. - Lotardo, Elizabeth; Earle McLeod, Lisa (linkedin.com, 2017)
Learn how to add value and differentiate a sales pitch. Explore crafting an opening statement, asking the right questions, and asking for the business.